Improving the Learning Concentration of Children Aged 3–4 Years through Outdoor Activities Based on Gross Motor Skills at PAUD Plus Az-Zalfa Pacitan - Nia Anugrah Putri; Septyana Tentiasih (Manunggal Halim Jaya, 2026)
This study aims to examine the effectiveness of gross motor-based outdoor activities in improving the learning concentration of children aged 3–4 years at PAUD Plus Az-Zalfa Pacitan. The research employed a quantitative approach with a quasi-experimental design, specifically a nonequivalent control group design. The sample consisted of 42 children divided into two groups (Class A and Class B), namely an experimental group and a control group, each consisting of 21 children. The instrument used was an observation sheet measuring learning concentration with indicators of focus, following instructions, and task completion. The data were analyzed using a paired sample t-test. The results showed a significant improvement in the experimental group, with an average increase of 9.95 compared to 1.67 in the control group. Statistical analysis revealed a significance value of p < 0.001. These findings indicate that gross motor-based outdoor activities are effective in enhancing the learning concentration of early childhood learners.